Monitoring large-scale on-farm performance of improved forage varieties in western Kenya - Karimi, Peggy; Odhiambo, Ruth; Paul, Birthe K. (Bioversity International and the International Center for Tropical Agriculture, 2021)
Inadequate availability of livestock feed is a major constraint to livestock rearing on smallholder farms in western Kenya. Breeding efforts have resulted in improved forage grass varieties with the potential for highly-nutritious feed that can increase dairy productivity. However, translating the production levels of these forage grasses from those obtained on research stations to the farm level remains a challenge. Unlike on research stations, forage production at farm level takes place under heterogeneous conditions, including variability of soils, climatic factors and farmers’ management practices among farmers, making it difficult to reach the scale needed to support adequate livestock rearing in the region. The objective of this study was to understand the effect of on-farm heterogeneity on the yield of Panicum Grass (Panicum maximum spp.) and Brachiaria spp. varieties in western Kenya. The study — which was conducted as part of a broader research project aimed at integrating improved forage grasses into mixed crop-livestock systems in Kenya and Ethiopia — tested the on-farm performance of two Panicum Grass varieties (P. maximum, Mombasa and P. maximum, Tanzania) and three Brachiaria Grass varieties (Cayman, Mulato II and Xaraes) in four counties of western Kenya, namely Kakamega, Bungoma, Busia and Siaya between October 2020 and May 2021. A scoping survey was conducted among 480 farmers, who received planting material, from which a further 169 farmers were selected for on-farm monitoring. Data on plant height, total fresh weight and dry matter yield was collected at intervals of six weeks. Information on agronomic practices among the farmers such as weeding frequency, and fertilizer / manure application was obtained through regular surveying. Soil was sampled and analysed for selected physical and chemical properties. Data was subjected to analysis of variance (ANOVA), and analysis of repeated measures. Study results will provide insights into forage grass production under heterogeneous farmer environments, helping to guide decision making among scientists, development professionals and policy makers in better designing, targeting and scaling forage grass technologies and practices.